Guns and butter - but no margarine: The impact of Nazi economic policies on German food consumtion, 1933-38 - Mark Spoerer; Jochen Streb (Universität Hohenheim, Forschungszentrum Innovation und Dienstleistung (FZID), 2010)
The German population's material standard of living during the 'peace years' of the Nazi regime (1933-38) is much debated. We use hitherto disregarded consumption data and the axiom of revealed preferences to test whether the material standard of living improved. We find that the food consumption bundle realized in 1935-36 must have been inferior to that of 1927-28 although GDP per capita was much higher. Even in 1937-38 consumers were probably worse off compared to 1927-28. We conclude that increasing consumption constraints forced German consumers to a diet and thus to a material standard of living that were much more frugal than national income figures suggest.
urn:nbn:de:bsz:100-opus-5310
Keywords: N34; D12; P46; 330; Nahrungsmittelversorgung; Lebensstandard; Wirtschaftsgeschichte; Deutschland (bis 1945)